2018
DOI: 10.1093/ecco-jcc/jjy031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Faecal Microbiota Transplantation for Treatment of Clostridium difficile Infection in Patients With Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis of Cohort Studies

Abstract: FMT is an effective therapy for CDI in patients with IBD. Well-designed randomised controlled trials and well-conducted microbiological studies are needed to validate its efficacy and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 45 publications
0
36
0
1
Order By: Relevance
“…CDI is more prevalent in patients with IBD123 and is associated with disease recurrence, more severe disease course, longer duration of hospitalisation and higher rates of colectomy and mortality 123 124. Although FMT effectively treats CDI in patients with IBD, efficacy may be lower than in patients without IBD, and independent of immunosuppressive therapy 125 126. FMT was strongly recommended in recurrent CDI complicating IBD and repeated FMT may be necessary 125 127.…”
Section: Resultsmentioning
confidence: 99%
“…CDI is more prevalent in patients with IBD123 and is associated with disease recurrence, more severe disease course, longer duration of hospitalisation and higher rates of colectomy and mortality 123 124. Although FMT effectively treats CDI in patients with IBD, efficacy may be lower than in patients without IBD, and independent of immunosuppressive therapy 125 126. FMT was strongly recommended in recurrent CDI complicating IBD and repeated FMT may be necessary 125 127.…”
Section: Resultsmentioning
confidence: 99%
“…In relation to treating rCDI with FMT in IBD patients, a meta-analysis showed that FMT is equally effective for treating rCDI in patients with IBD (initial cure rate of 81%) when compared with those without IBD (55). FMT was equally efficacious in treating rCDI for CD and UC patients.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Faecal microbiota transplantation has also been adopted in human and mouse models [ 479 ] and has been shown to be effective in dealing with Clostridium difficile infect in IBD [ 480 , 481 , 482 ].…”
Section: Aberrant Mucin Glycosylation and Disease In The Gastroinmentioning
confidence: 99%